1991
DOI: 10.1021/ic00004a036
|View full text |Cite
|
Sign up to set email alerts
|

Thermally activated magnetic interactions in a one-dimensional semiconductor. Structural, charge-transport, and magnetic studies of bis[(tetramethylporphyrinato)copper] perrhenate

Abstract: Electrochemical oxidation of (5, IO, I5,20-tetramethylporphyrinato)copper(II), Cu(tmp), in the presence of the perrhenate ion affords the new molecular conductor [Cu(tmp)12 [Re04]. The compound is composed of partially oxidized Cu(tmp) cations stacked metal-over-metal and surrounded by chains of Reo, anions. Single-crystal, room-temperature conductivity along the needle (crystallographic c) axis averages 40 Q-' cm-I, lower than the values previously reported for Ni(tmp)-based conductors. The conductivity is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…In the case of Mo 2 Cl 10 4-, the S ) 3 state lies lowest, and hence the global minimum in the broken-symmetry state is found at large rMo-Mo (4.1 Å), where all metal-based electrons are completely localized. The ground state is therefore distinctly different from that of the isovalent face-shared species, Mo 2 Cl 9 3 in which all metal-based electrons are delocalized, and the Mo-Mo separation is short.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…In the case of Mo 2 Cl 10 4-, the S ) 3 state lies lowest, and hence the global minimum in the broken-symmetry state is found at large rMo-Mo (4.1 Å), where all metal-based electrons are completely localized. The ground state is therefore distinctly different from that of the isovalent face-shared species, Mo 2 Cl 9 3 in which all metal-based electrons are delocalized, and the Mo-Mo separation is short.…”
Section: Resultsmentioning
confidence: 86%
“…In recent years the chemistry of systems containing two or more transition metal centers has expanded rapidly . Small clusters of metal atoms have obvious applications in the study of metal surfaces, electronic devices, and catalysts, as well as the relatively new discipline of bioinorganic chemistry . For example, the oxygen-transport proteins hemerythrin and hemocyanin feature diiron and dicopper sites, respectively, while manganese catalase contains two manganese ions .…”
Section: Introductionmentioning
confidence: 99%
“…The interplanar distances in epitaxyally grown phthalocyanine films 4,20 and stacked unidimensional porphyrin crystals 40,41 were estimated to be approximately 3.2 and 3.5 Å, respectively. In the case of a rodlike nematic mesogenic porphyrin phase, Bard and co-workers reported that the value increases to about 4 Å.…”
Section: Resultsmentioning
confidence: 98%
“…These oxidation states were veri®ed by manual inspection, with reference to the CSD compound name ®eld. The oxidation state was calculated incorrectly for the bis(1,2,6,7 -tetracyano -3,5 -diimino-3,5 -dihydropyrrolizinido-N,N H ) Cu(2) complexes VAVKOS [Bonamico et al, 1989; BVS 1.13 using the R 0 value for Cu(1), 1.84 R 0 of Cu(2)], WEGDUH [Bonamico et al, 1993;1.12 R 0 of Cu(1), 1.82 R 0 of Cu(2)] and the 5,10,15,20-tetramethylporphyrinato Cu(2) complex JILGAM [McGhee et al, 1991; BVS for R 0 of Cu(1) 1.10, R 0 of Cu(2) 1.78], although the BVS with Cu(2) R 0 values are in acceptable agreement. Similar problems were encountered for Ni complexes using equation 4 (Naskar et al, 1997).…”
Section: Resultsmentioning
confidence: 99%